Property Rights, Finance, and Entrepreneurship - Simon Johnson; John McMillan; Christopher Woodruff (Center for Economic Studies and ifo Institute (CESifo), 1999)
Is investment constrained more by insecure property rights or by limited external finance? For five transition economies in Eastern Europe and the former Soviet Union we find that weak property rights limit the reinvestment of profits in startup ma nufacturing firms. Access to credit does not appear to explain differences in investment. At least in the early stages of post-communist reform, retained earnings appear to have been enough to finance the investments that managers wanted to make.
Keywords: 330